The Influence of Leadership Style and Organizational Culture on Employee Performance with Work Climate as an Intervening Variable in BPJS Kisaran Branch and Padang Sidimpuan Branch - Edwin Saputra; Mesra B (Lafadz Jaya Publisher, 2024)
Humans always live in organizations in their daily lives because humans are social creatures who were created to live in society. This is clearly visible in household life, social organizations, and even when someone starts working. There is a phenomenon of different leadership styles and organizational culture at BPJS employment in Kisaran and Padang Sidempuan, which makes researchers interested in discussing it. As discussed above, leadership style will influence everything in the organization. Organizational culture also influences the leadership style of an organization, so it also influences employee performance and work climate. The firm leadership style of the Padang Sidempuan branch of BPJS forms a strict organizational culture, while the Kisaran branch of BPJS has a softer leadership style, influencing the organizational culture to become more relaxed. But of course this is not the only reason why there are differences in the two branches between Padang Sidempuan and Kisaran. The results of this research are as follows: Organizational Culture has a positive and significant effect on Work Climate with an original sample value of 0.766 and ap value of 0.000 <0.05. Organizational culture has a positive and insignificant effect on employee performance with an original sample value of 0.082 and ap value of 0.319 > 0.05. Leadership Style has a positive and significant effect on Work Climate with an original sample value of 0.168 and ap value of 0.025 <0.005. Leadership style has a positive and insignificant effect on employee performance with an original sample value of 0.139 and ap value of 0.160 > 0.05. Work Climate has a positive and significant effect on Employee Performance with an original sample value of 0.649 and ap value of 0.000 <0.05. Organizational culture has a positive and significant indirect effect on employee performance through work climate with a value of 0.497 and ap value of 0.000. Leadership Style has a positive but not significant indirect effect on Employee Performance through Work Climate with an original sample value of 0.109 and ap value of 0.066.